(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the context of hospitals, the client refers to the patient, who holds utmost significance as hospitals rely on them for their sustenance. Indirect marketing is carried out by the patients. The majority of patients select hospitals based on word-of-mouth and recommendations from other patients. Ensuring patient happiness is crucial and essential for the success of a Healthcare organisation. Health organisations encounter substantial obstacles in managing consumer behaviour (patients) who perceive quality as the primary factor for distinguishing the services they offer. Multiple studies demonstrate that patients who are content get quicker and more successful recovery from the administered medication. This fosters a positive reputation for the organisation, generates favourable word-of-mouth, and attracts a greater number of patients to the hospitals. Patient satisfaction is indicative of staff contentment and effective job performance. Therefore, by ensuring patient satisfaction, a hospital may guarantee its success. Hence, it is imperative to conduct surveys to obtain continuous feedback on patient satisfaction, as well as their perspective and expectations